Contemporary antiplatelet therapy for secondary stroke prevention: a narrative review of current literature and guidelines. Issue 5 (7th April 2022) - Shah, Jay; Liu, Shimeng; Yu, Wengui
Abstract : Antiplatelet therapy is one of the mainstays for secondary stroke prevention. This narrative review aimed to highlight the current evidence and recommendations of antiplatelet therapy for stroke prevention. We conducted advanced literature search for antiplatelet therapy. Landmark studies and randomised controlled trials evaluating antiplatelet therapy for secondary stroke prevention are reviewed. Results from Cochrane systematic review, pooled data analysis and meta-analysis are discussed. Single-antiplatelet therapy (SAPT) with aspirin, aspirin/extended-release dipyridamole or clopidogrel reduces the risk of recurrent ischaemic stroke in patients with non-cardioembolic ischaemic stroke or transient ischaemic attack (TIA). Dual-antiplatelet therapy (DAPT) with aspirin and clopidogrel or ticagrelor for 21–30 days is more effective than SAPT in patients with minor acute noncardioembolic ischaemic stroke or high-risk TIA. Prolonged use of DAPT is associated with higher risk of haemorrhage without reduction in stroke recurrence than SAPT. Compared with placebo, aspirin reduces the relative risk of recurrent stroke by approximately 22%. Aspirin/dipyridamole and cilostazol are superior to aspirin but associated with significant side effects. Cilostazol or ticagrelor might be more effective than aspirin or clopidogrel in patients with intracranial stenosis. SAPT is indicated for secondary stroke prevention in patients with non-cardioembolic ischaemic stroke or TIA. DAPT with aspirin and clopidogrel or ticagrelor for 21–30 days followed by SAPT is recommended for patients with minor acute noncardioembolic stroke or high-risk TIA. Selection of appropriate antiplatelet therapy should also be based on compliance, drug tolerance or resistance.